Significados construídos en indígenas universitarios sobre sustancias psicoactivas y programas de prevención (2017)
ABSTRACT: Various ethnic groups are present at universities, and this generates a setting for cultural diversity. It also leads to the need to understand meanings regarding the use of traditional plants and the difference between this practice and the use of psychoactive substances (pas) by college indigenous students for recreational purposes. Objective: To analyze the meanings constructed by indigenous students regarding the use of pas, the use of traditional plants and prevention programs at Universidad de Medellin. Methodology: This research was qualitative; it implemented grounded theory as a methodological tool. The study used a theoretical sampling technique based on 602 indigenous students. A representative sample was taken based on regional and student qualities of 16 indigenous students. Researchers implemented data gathering techniques such as interviews and focus groups, which allowed coding and categorizing of the information that was to be analyzed. Results: Indigenous students recognize that in a university setting, social ties and comprehensiveness of prevention programs are determining factors in the use of pas. Conclusions: participants consider that the Student Union must create specific programs to strengthen indigenous culture to address and respect the different meanings. Key words: Psychoactive substances, traditional plants, college indigenous students, Student Union.